MICROBICIDAL EVALUATION OF PLANT EXTRACTS - IRON METAL IONS COMPLEX - Sharma, Amarish Kumar; Kaur, Jasvir; Sharma, Anjana Rana (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â  Â Objective: The aim of this study is to screen and evaluate the antimicrobial or microbicidal effect of plant metabolites, conjugated with essential iron metal ions. Methods: First batch of study includes screening of antimicrobial activity of leaves of mint (Mentha), methi (Trigonella foenum-graecum), and neem (Azadirachta indica) against Bacillus, Aspergillus, and Rhizopus sp., respectively. Inhibition of microbial growth and propagation was investigated using agar well diffusion method (minimum inhibitory concentration evaluation). Antibiotic agent, streptomycin sulfate, and antimycotic agent, and fluconazole was used as a positive control. The polar, non-polar, and aqueous extracts of plants leaves of abovementioned plant species were screened for their antibacterial activity against Bacillus sp. and antifungal activity against Aspergillus and Rhizopus sp. and their mix culture, respectively. Second batch of study includes evaluation of combinatorial effect of plant extracts of mint (Mentha piperita), methi (T. foenum-graecum), and neem (A. indica) complexed with ferric ions (Fe3+, Iron metal ions) in concentrations at acceptable dosage range. Results: The antibacterial and antifungal activity of the plants leaves extracts in different combinations was evaluated. The plant extracts from selected plant of neem, methi, and mint after conjugation with essential iron metal ions and at a concentration of 100 mg/ml show an enhanced microbicidal (2-3 fold) activity compared to only plant extracts used in the experiment. Conclusion: Based on the above investigation, it can be concluded that the plant extracts possessing antimicrobial property when conjugated with essential metal ions (iron metal ions) show enhanced antimicrobial efficacy compared to only plant extracts used. The result from this investigation could be very helpful in the food preservation and packaging industry.